x(x²-y²)²+y(x²-y²)²=(х²-у²)²(х+у)=((х-у)(х+у))²(х+у)=(x+y)³(x-y)² правая часть равна левой Представьте в виде многочлена: a) (p+k-4)(p+k+4)=(p+k)²-16=p²+2pk+k²-16 б) (a-b+5)(a+b+5)=(a+5)²-b²=a²+10a+25-b² в) (x-y-6)(x+y+6)=x²-(y+6)²=x²-(y²+12y+36)=x²-y²-12y-36 г) (m-n+2)(m+n-2)=m²-(n-2)²=m²-(n²-4n+4)=m²-n²+4n-4
-1 2 x∈(-1;2) 3)(6x²-15x+19)/(3x²-6x+7)<2 (6x²-15x+19-6x²+12x-14)/(3x²-6x+7)<0 (5-3x)/(3x²-6x+7)<0 5-3x=0⇒3x=5⇒x=5/3 3x²-6x+7=0 D=36-84=-48<0⇒3x²-6x+7>0 при любом х 5-3x<0 x>5/3 x∈(5/3;∞)
ответ: f(3)=9/3+6=3+6=9, f(-1)=1/3-2=1/3-6/3=-5/3=-1 2/3.
Объяснение: